Nanostructures Fabrication and Analysis - Nejo, Hitoshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The main theme of this book is the exploration the underlying physical laws that permit the fabrication of nanometer-scale structures. As researchers attempt to fabricate nanometer-scale structures which do not exist per se, they must still employ the natural laws to fabricate them through processes such as self-assembly. So it turns out that our techniques for fabrication of nanometer-scale structures are not artificial but actually rely on the natural laws. We even find that nanometer-scale structures, e.g. fullerenes, are fabricated in nature beneath the surface of the Earth. This fact may be called the ubiquity of the nanometer-scale structures. The topics presented in the book include: scanning probe-related and near-field techniques, nanolithography, self assembling and design of novel nanostructures, as well as new nanodevices and their application.
Atomic-Scale Chains: Fabrication and Evaluation Technologies -- Nanolithography -- Adsorption Behavior of Single Molecules on Surfaces Formed by Molecular Assemblies Studied by Scanning Tunneling Microscopy -- Fabricating Nanostructures via Organic Molecular Templates -- Carbon Nanotubes -- Calculating Transport Properties of Nanometer-Scale Systems: Nanodevice Applications of Carbon Nanotubes and Organic Molecules -- Molecular Wires.
Keywords: Nanotechnology; Condensed matter; Engineering; Nanotechnology; Condensed Matter Physics; Engineering, general